The Evolution of Drug Discovery : From Traditional Medicines to Modern Drugs - Enrique Raviña Rubira (Wiley-VCH, 2011)
The discovery and use of medicines is just as fascinating a human scientific endeavor as space flight or the tracing of human evolution. It is also the everyday task of hundreds of thousands of pharmacists, pharmaceutical chemists and researchers worldwide.Based on his profound knowledge of past and present paradigms in the development of medicines, Enrique Ravina takes the reader from the very beginnings of pharmacology to the multibillion-dollar business it represents today. Recounting the often spectacular successes and failures of innovative drugs as well as the people who discovered them, he brings abstract science to life in anecdotal form.For anyone with a more than superficial interest in the science of drugs and all those interested in knowing how drugs have been developed, how they have reached us, and became part of our daily life. This book is beautifully illustrated, containing many rare and historical photographs of drugs and their discoverers, and abounds with references to the primary literature, listing seminal publications alongside more modern reviews for readers seeking further details.